Peran Elit Politik Partai dalam Pemenangan Pemilukada Kabupaten Padang Lawas Utara 2008 - HARAHAP, PAHRUR ROJI (Politeia: Jurnal Ilmu Politik, 2013)
Pemilukada be held in Padang Lawas Utara in 2008. This is a study about the role of political elites in Pemilukada (the election of regional head) Padang Lawas Utara. The focus is to de-scribe the role of the elite (political parties) in the procces of winning pemilukada. This study is using political elite aproach. Colecting data of this study is using field research, eg. observa-tion, interview and study documents. The analysis using descriptive analysis. This study found that there are three important explanation about the role of elites to manage few leap to win pemilukada. First, internally, the elite contribute to bring over the main candidate to win inter-nal mechanism for certain (in internal party); Second, the elite set up the direction of coalition between political parties; Third, the elite have participated in defining campaign strategy.Keywords: Political strategy, campaign, political elite.